The impact of occlusive vs non‐occlusive application of 5‐aminolevulinic acid (BF‐200 ALA) on the efficacy and tolerability of photodynamic therapy for actinic keratosis on the scalp and face: A prospective within‐patient comparison trial. Issue 1 (13th October 2020) - Meierhofer, C.; Silic, K.; Urban, M. V.; Tanew, Adrian; Radakovic, Sonja
Abstract: Background: Photodynamic therapy (PDT) is an effective treatment for actinic keratoses (AK). PDT is usually performed with occlusion of the photosensitizer prior to subsequent illumination. Objectives: This study aimed to compare the efficacy and tolerability of occlusive versus non‐occlusive application of a 5‐aminolevulinic gel (BT‐200 ALA) for PDT of multiple AK on the scalp or face. Methods: Prospective, investigator‐blinded, within‐patient comparison study on 45 patients. PDT with occlusion of ALA was performed in a target area on one randomized side of the scalp or face. One week later a contralateral target area received the same treatment except that no occlusion of the ALA gel was performed. 3 and 6 months after PDT, the clearance rate of a predetermined target lesion and the total clearance rate of all AK within the treated areas were determined. PDT‐induced pain and skin phototoxicity and cosmetic outcome were also recorded. Results: Clearance rate of the target AK and total AK clearance rate at 3 months after PDT was 88.4% and 90.6% for occlusive PDT and 58.1% ( P  = .001) and 70.4% ( P  = .04) for non‐occlusive PDT. The corresponding values at 6 months after PDT were 69.7% and 72.1% for occlusive PDT and 30.2% ( P  < .001) and 35.6% ( P  = .001) for non‐occlusive PDT. Pain score and skin phototoxicity were significantly higher after occlusive ALA application. No difference was observed with respect to cosmetic outcome. Conclusions: Occlusive application of ALA significantly improves the efficacy of PDT but is associated with more pain and increased phototoxicity.